PENERAPAN KATA MAAF, TOLONG DAN TERIMA KASIH DALAM PEMBENTUKAN KARAKTER SOSIAL ANAK: kata maaf, tolong, terima kasih, karakter sosial - Bandi, Arifa; Lina, Mawardah; Lutfiana, Lestari; Nur, Wahyuni; Arifatur, Rohmaniah Arifatur (WIDYA DIDAKTIKA - Jurnal Ilmiah Kependidikan, 2025)
In an effort to form a quality generation, character education must be carried out from an early age. However, education or learning about social character as the basis of life in society has very limited sources and can only be obtained through education at school or education from parents in the family. This study uses a research method based on library research. Library-based research is conducted by reviewing literature or articles that support the research title. Data collection techniques used in the study are 1) reading, 2) taking notes, 3) processing research materials to achieve relevant results. Primary data collection in this study, from 17 articles and 1 book. The results of this study: First, the habit of using the word "Sorry", is carried out through the guidance of parents or educators. Second, the habit of saying the word "Thank you" is carried out by providing examples of activities for children to always say thank you. Third, the habit of using the word "Please" is carried out through habituation activities by providing examples to children. Fourth, the habit of saying the word "Permission" is carried out by providing understanding to children.